2009
DOI: 10.1007/s12291-009-0054-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oxidative stress and antioxidant status of pregnant women suffering from malaria in Cameroon

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…falciparum infection might cause oxidative stress in placenta tissue. These observations corroborate previous findings where associations between peripheral plasma levels of MDA and cerebral malaria in children [ 14 ] as well as malaria infection during pregnancy in women have been reported [ 10 ]…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…falciparum infection might cause oxidative stress in placenta tissue. These observations corroborate previous findings where associations between peripheral plasma levels of MDA and cerebral malaria in children [ 14 ] as well as malaria infection during pregnancy in women have been reported [ 10 ]…”
Section: Discussionsupporting
confidence: 92%
“…However, Tiyong Ifoue et al . [ 10 ] reported an imbalance between oxidants and antioxidants with regards to malaria in women during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…4-HNE has received little attention by malariologists as yet, although elevated levels of free, unconjugated 4-HNE had been described in RBCs of P. vinckei -infected mice as early as 1988 [ 41 ]; one study reported the growth inhibition of in vitro cultured parasites by 4-HNE [ 42 ], and the general presence of oxidative stress in malaria was detected long ago [ 43 46 ].…”
Section: 4-hne Production In Malariamentioning
confidence: 99%
“…Oxidative stress, generally described as an imbalance between the formation of free radicals, such as reactive oxygen species (ROS), and protective antioxidant defense molecules within cells and tissues, leads to cellular damage to lipids, proteins, RNA, and DNA. Recently, oxidative stress has been documented to play a crucial role in pregnancy outcome in some mouse models of PM [24,26,27] and is implicated in human populations experiencing malaria during pregnancy [18,19] as well as other types of pregnancy complications [38][39][40]. To interrogate the role of oxidative stress in our models, placentae from serially sacrificed mice were evaluated for alterations in antioxidant gene expression by RT-qPCR (Fig.…”
Section: Resultsmentioning
confidence: 99%